Consumers’ perspective and perception of Malaysian cafe - Khor, Sujian (2017)
While independent café scene is blooming in Malaysia, many existing cafés are suffering to sustain the business. One of the reasons is the bad economy situation in Malaysia which is causing the low consumer spending confidence and high currency exchange rate for imported goods do not help either. As the café scene is relatively new in Malaysia, there are many cafes that are inspired by oversea cafes spent huge investment in coffee equipment. However, the return of investment of a café business is relatively slow. To achieve competitive advantage, café business owners should invest effectively on the resources that can bring higher significant result to the café. The present research project was aimed to discover the evaluation of quality in different dimensions from customer perspective: food quality, service quality, and quality of physical environment. It involves the impact of three quality dimensions on café image, customer perceived value, customer satisfaction, and behavioural intentions. A total of 216 respondents were engaged in this study. Structural equation model showed that food quality, services quality, and quality of physical environment are the determinant of café image. The mediation test confirmed that service quality has direct impact on customer satisfaction. Café image was served as full mediator for food and physical environment with customer satisfaction. The multi-group comparison test found two different types of consumer groups: Frequent and non-frequent café patrons. Frequent café patrons prioritized service as most important factor on café image, followed by food and physical environment. The only interest of non-frequent café patrons has in café is food quality. The quality of physical environment was found to have significant negative relationship with customer perceived value for non-frequent café patrons. Generally, customer perceived value did not show significant strong relationships in the hypothesized model. The outcome of this study clearly showed that service quality is the most important factor in café industry.